Prevention of stunting in children by making processed products from traditional plants - Aqila Pradita Hutami Efendi; Sindi Ayu Safitri; Oby Ihza Putra; Cagiva Geofani; Fenny Widya Santoso; Ni Made Ayu Nila Septianingrum (Community Empowerment, 2022)
Stunting is a condition of failure to thrive in children under five due to malnutrition in the womb. Stunting cases in Indonesia have decreased every year, but the handling in each region has not been evenly distributed, so there are still many stunting cases, especially in villages. The purpose of this service is to succeed in government programs in reducing stunting rates in Somoketro Village, Salam District, Magelang Regency and to improve community skills in innovating food manufacturing to increase nutritional intake. The service is carried out using the Participatory Rural Appraisal (PRA) method which actively involves the community. The results of this service have a positive impact, namely increasing community knowledge and innovation about stunting prevention by utilizing Family Medicinal Plants (TOGA).